2021
DOI: 10.1101/2021.03.01.433475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypothalamic Overexpression of Neurosecretory Protein GL Leads to Obesity in Mice

Abstract: Introduction: The mechanisms underlying obesity are not fully understood, necessitating the creation of novel animal models for investigation of metabolic disorders from the cellular-molecular to behavioral levels of analysis. We have previously found that neurosecretory protein GL (NPGL), a newly-identified hypothalamic neuropeptide, is involved in feeding behavior and fat accumulation in rats. Given the broad availability of genetic tools in mice, the present investigation sought to establish a mouse model o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…These data imply that NPGL affects multiple tissues, such as the intestine and WAT, to orchestrate glucose absorption and carbohydrate use for efficient de novo lipogenesis under NC conditions. In contrast to our previous study demonstrating that Npgl overexpression is unable to affect the blood glucose level in NC-fed mice [27], we again emphasize the finding that Npgl overexpression alleviated glucose intolerance, insulin resistance, and hyperglycemia in HFD-fed mice at the experimental end point of the present study. Over the past 30 years, novel molecular mechanisms linking obesity and its related disorders have been deciphered.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…These data imply that NPGL affects multiple tissues, such as the intestine and WAT, to orchestrate glucose absorption and carbohydrate use for efficient de novo lipogenesis under NC conditions. In contrast to our previous study demonstrating that Npgl overexpression is unable to affect the blood glucose level in NC-fed mice [27], we again emphasize the finding that Npgl overexpression alleviated glucose intolerance, insulin resistance, and hyperglycemia in HFD-fed mice at the experimental end point of the present study. Over the past 30 years, novel molecular mechanisms linking obesity and its related disorders have been deciphered.…”
Section: Discussioncontrasting
confidence: 79%
“…Hypothalamic neuropeptides predominantly control feeding behavior and metabolism and are closely linked to obesity development [ 28 , 29 ]. We recently demonstrated that hypothalamic overexpression of Npgl , a novel small secretory protein precursor gene, elicits food intake and fat accumulation in mice [ 27 ]. However, the effect of NPGL on insulin sensitivity and glucose homeostasis has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations